Exploration and Discussion on Key Technologies for Satellite-Terrestrial Integration Networking - SONG Yaqin; XU Hui; LIU Xianfeng; CAO Caihong; CHENG Zhimi; WANG Hucheng (天地一体化信息网络)
For the future, mobile communication networks will have the ability to provide communication services with beyond connectivity, as well as to realize the system level integration of satellite communication and terrestrial communication, so an integrated satellite and terrestrial network architecture that included multiple elements such as connectivity, intelligence, sensing, computing, and data was proposed. Based on the proposed network architecture, several key technologies for satellite-terrestrial integration networking were discussed, included intelligent management and control technology for satellite and ground collaboration, a high dynamic network slicing technology for integrated satellite-terrestrial, and in response to the differentiated network service requirements of user services for integrated satellite and terrestrial network, the potential development patterns between distributed autonomous and network slicing technologies were discussed. Then, onboard lightweight core network technology was introduced. Finally, the feasibility of multi-service network slicing coexistence and on-board lightweight core network were verified through a self-developed mobile communication network platform.